Algoritmo para el análisis probabilístico en sistemas de distribución con generación distribuída - Meneses, Cesar Augusto Peñuela [UNESP]; Echeverri, Mauricio Granada; Mantovani, José Roberto Sanches [UNESP] (My University, 2011)
In this paper an efficient algorithm for probabilistic analysis of unbalanced three-phase weakly-meshed distribution systems is presented. This algorithm uses the technique of Two-Point Estimate Method for calculating the probabilistic behavior of the system random variables. Additionally, the deterministic analysis of the state variables is performed by means of a Compensation-Based Radial Load Flow (CBRLF). Such load flow efficiently exploits the topological characteristics of the network. To deal with distributed generation, a strategy to incorporate a simplified model of a generator in the CBRLF is proposed. Thus, depending on the type of control and generator operation conditions, the node with distributed generation can be modeled either as a PV or PQ node. To validate the efficiency of the proposed algorithm, the IEEE 37 bus test system is used. The probabilistic results are compared with those obtained using the Monte Carlo method. © 2012 2006, Revista DYNA.
Algorithm for probabilistic analysis of distribution systems with distributed generation
Keywords: Distributed generation; Distribution; Power flow; Probabilistic; Three-phase systems; Weakly meshed systems